2020
DOI: 10.1002/rcr2.649
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic visualization of a cavity in entirety: an unusual finding

Abstract: Key message It is unusual to be able to visualize an entire cavity with such clarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Bronchoscopic appearance of a lung cavity has been previously described in a few reports. 8 10 Previous reports have used different terminologies in describing the inside of lung cavity seen on bronchoscopy. For example, a web-blog post described it as the “black hole sign” referring to the darkness of the inside of the cavity due to lack of reflection of light from the bronchoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopic appearance of a lung cavity has been previously described in a few reports. 8 10 Previous reports have used different terminologies in describing the inside of lung cavity seen on bronchoscopy. For example, a web-blog post described it as the “black hole sign” referring to the darkness of the inside of the cavity due to lack of reflection of light from the bronchoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopic visualization of the inner cavity is extremely unusual because it must be communicated with a dilated bronchus to introduce a bronchoscope. A few bronchoscopic studies showed inside the tuberculous cavity is composed of caseum necrotic debris [ 5 ]. In this patient, the underlying bronchiectasis allowed the passage of a bronchoscope into the cavity and visualization of lung architectural destruction.…”
Section: Introductionmentioning
confidence: 99%